Multi-temporal analysis of submarine sand dunes morphodynamics (Bay of Brest, Brittany, France): A marker of sediment pathways in a macrotidal environment open to sea swells. (5th September 2022) - Belleney, Déborah; Ehrhold, Axel; Le Dantec, Nicolas; Le Roy, Pascal; Jouet, Gwenael
Abstract: Sediment structures including submarine banks and dune fields are ubiquitous on tide-dominated continental inner shelves such as in the Iroise Sea. These are of current interest to human activities in several respects: they constitute an obstacle to navigation, they are dredged for beach nourishment or exploited for marine aggregates. In addition, the morphodynamic characterising of these sedimentary structures improves the knowledge of the sediment transfers that occur in coastal areas. This study documents a submarine sand dune field located along the northern flank of the Goulet channel connecting the Bay of Brest to the Iroise Sea and the Bay of Biscay. Subject to a macrotidal regime with strong currents, and to large waves during storm events, this sedimentary system features large dunes with very high migration rates. The analysis of six bathymetric datasets (from March 2013 to October 2019) allows specifying the morphodynamic characteristics of this small dune field about 3.5 km in length and 500 m in width. These dunes have heights on the order of 0.5 m–3.7 m with migration rates that can vary significantly within the range from 10 m/yr to 70 m/yr. The results highlight that the ebb tidal current and slope of the channel are the main factors controlling the evolution of these biogenic sandy structures migrating offshore (SW). Furthermore, seasonal variations in coastal hydrodynamics forcing, driven by tidal currents, appear to affect the temporal and spatial evolution of the dunes at this shorter time scale. This paper proposes a model of sediment transport patterns at the mouth of the bay of Brest according dune field characteristic, strong ebb current and residual tidal gyre. Highlights: Channelised tidal currents in macrotidal environment induce large variation in dune migration rates across a dune field at the outlet of the Bay of Brest. Tidal gyre in the shallower nearshore terrace contributes to the recirculation of sediment from dune field through external pathways. The steep slopes of the channel impact dune migration rates, with reduced rates on the negative slopes and increased rates on the positive slopes.